YOSH BASKETBOLCHILARNI TAYYORLASHDA JISMONIY SIFATLARNI RIVOJLANTIRISH (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
This article highlights the importance of developing physical qualities in young basketball players. Methods for improving speed, strength, endurance, agility, and flexibility are analyzed. The article also provides information about the origin of basketball, the history of the Olympic Games and World Championships, leading basketball countries, and the development of basketball in Uzbekist